2010
DOI: 10.1007/s13365-010-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Viral genome silencing by neuronal sirtuin 1

Abstract: Neurotropic viruses remain dormant in sensory neurons for years, but upon reactivation, they can produce multiple disease states including pain symptoms. Latent viral DNA is extrachromosomal, maintained as a circular episome bound to histones. Here, we show the regulation of an adenoviral genome by the nicotinamide adenine dinucleotide (NAD(+))-dependent histone deacetylator Sirt1 in dorsal root ganglion neurons. Pharmacological modulation of Sirt1 and Sirt1 overexpression both affected viral transgene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Silencing RNA (siRNA) knockdown of all seven human sirtuins (SIRT1–7) has been shown to increase AdV-C5 titers by 1.5- to 3-fold [88]. In the same vein, activation of sirtuins through resveratrol treatment inhibits adenovirus DNA replication [89, 90]. Another NAD + -dependent enzyme to have been studied in lytic infection is Poly (ADP-Ribose) Polymerase 1 (PARP1); the AdV E4orf4 protein has been found to increase production of viral progeny through inhibition of PARP1, which is activated by the infection-induced DNA damage response (DDR) [91].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing RNA (siRNA) knockdown of all seven human sirtuins (SIRT1–7) has been shown to increase AdV-C5 titers by 1.5- to 3-fold [88]. In the same vein, activation of sirtuins through resveratrol treatment inhibits adenovirus DNA replication [89, 90]. Another NAD + -dependent enzyme to have been studied in lytic infection is Poly (ADP-Ribose) Polymerase 1 (PARP1); the AdV E4orf4 protein has been found to increase production of viral progeny through inhibition of PARP1, which is activated by the infection-induced DNA damage response (DDR) [91].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the reports available in literature in which SIRT1 and its positive modulation by resveratrol inhibit varicella zoster virus replication, [24], human immunodeficiency virus type 1 (HIV-1) long terminal repeat (LTR) [25] transactivation, and viral transgene expression of adenovirus in neuronal cells [26], Shenk et al [27] patented the effects of the known sirtuin inhibitors EX-527, cambinol, tenovin-6, salermide, and of the SIRT1 activators resveratrol and the pyrroloquinoxaline CAY10602 ( Figure 1) in virus production. First, the authors demonstrated that the prominent positive effect on human cytomegalovirus (HCMV) replication in infected MRC5 fibroblasts was mainly observed when mitochondrial SIRT3--5 were inhibited by short interfering RNA (siRNA), thus indicating for the first time that the activation of those isoforms could be useful targets for antiviral therapy.…”
Section: Sirtuin Inhibitorsmentioning
confidence: 99%
“…However, SIRT1 has been implicated in the progression of human immunodeficiency virus 1 (HIV-1) [102,107,108,109], human papillomavirus (HPV) [110] and vesicular stomatitis virus (VSV) [111] infection. SIRT1 has also been proposed to control the reactivation of latent varicella zoster virus (VZV) in neurons through the reduction of intracellular NAD + levels [112]. Additionally, canine coronavirus (CCoV-II) infection has been shown to induce the expression of SIRT1, SIRT3 and SIRT4 [113], suggesting that the regulation of individual sirtuins is virus specific.…”
Section: Host Employment Of Hdacs and Acetylation In Defense Againmentioning
confidence: 99%